"When I Eat Well, I Will Be Healthy, and the Child Will Also Be Healthy": Maternal Nutrition among HIV-Infected Women Enrolled in a Livelihood Intervention in Western Kenya. Issue 4 (13th March 2020) - McDonough, Annie; Weiser, Sheri D; Daniel, Afkera; Weke, Elly; Wekesa, Pauline; Burger, Rachel; Sheira, Lila; Bukusi, Elizabeth A; Cohen, Craig R
ABSTRACT: Background: Food insecurity remains a major obstacle to achieving health and well-being for individuals living with HIV in western Kenya. Studies have shown that pregnant women are vulnerable to experiencing food insecurity worldwide, with significant consequences for both maternal and child health. The Shamba Maisha cluster randomized controlled trial in western Kenya (which means "farming for life" in Swahili) tested the effects of a multisectoral livelihood intervention consisting of agricultural and finance trainings, farm inputs, and a loan on health and food security among 746 farmers living with HIV in Kisumu, Homa Bay, and Migori Counties. Objectives: We conducted a qualitative substudy within the Shamba Maisha trial to understand the experiences and perspectives of pregnant women living with HIV enrolled in the trial. Methods: Thirty women who had experienced a pregnancy during the Shamba Maisha study period, comprising 20 women in the intervention arm and 10 women in the control arm, completed in-depth interviews using a semistructured interview guide. Results: Intervention participants interviewed noted improvements in maternal nutrition compared with previous pregnancies, which they attributed to the livelihood intervention. Key identified pathways to improved nutrition included improved access to vegetables, increased variety of diet through vegetable sales, and improved nutritional awareness. Women in the intervention arm also perceived increased weight gain compared with prior pregnancies and increased strength and energy throughout pregnancy. Conclusions: Livelihood interventions represent a promising solution to alleviate food insecurity for pregnant women in order to improve maternal and child health outcomes. This trial was registered at clinicaltrials.gov as NCT02815579.